Verification of Malus's Law using a LCD monitor and Digital Photography - Vertchenko,Larissa (2016)
An alternative laboratory experiment for verifying Malus's Law, as well as understanding concepts of photometry, polarization and image formation on liquid crystal displays using low cost materials is proposed. The experimental setup could be introduced to any undergraduate curriculum using readily available tools, such as a digital camera, polarizer removed from a cell phone and a LCD laptop screen. A fairly amount of photometric data was collected and analyzed by an astronomical image processing software resulting in a successful verification of Malus's Law.